Prototype of IoT-based Gas and Temperature Monitoring System for Genset Room with ESP8266 - Agus Pramono; Muhammad Zhiya Ulhaq; Gilang Dely Mukti (Universitas Islam Indragiri, 2026)
Generator rooms require strict environmental monitoring to ensure operational safety, as uncontrolled temperature and gas concentration conditions may pose risks of fire and workplace accidents. This study aims to develop an Internet of Things (IoT)–based generator room monitoring system capable of automatically and real-time monitoring temperature, humidity, and gas levels, with notifications delivered via a Telegram bot. The research method adopts a systematic approach through prototype development. The system utilizes DHT22 and MQ-2 sensors, a NodeMCU ESP8266 microcontroller, a buzzer, and is integrated with the Telegram Bot API. The testing results demonstrate that the device is able to responsively monitor environmental parameters, transmit real-time data to Telegram, activate the relay with a response time of 4–5 seconds, and provide automatic notifications when gas concentrations exceed safe thresholds with a delay of 1–2 seconds. Evaluation of the monitoring functionality and sensor data visualization through the Telegram application indicates that all sensor information is successfully displayed via the Telegram bot interface. Although data transmission from the sensors to the Telegram application is highly dependent on network connection stability, the experimental results show that the system is capable of delivering data with optimal response time.